The educator's guide to assessing and improving school discipline programs - Boynton, Mark, 1947- (Association for Supervision and Curriculum Development, 2007)
Blending research with teacher-developed strategies, this book helps teachers better understand students' cultural differences and turn educational challenges into educational opportunities.